2002
DOI: 10.1177/002580240204200207
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Fatal Head Injuries in Ibadan — A 10 Year Review

Abstract: Head injury is an important cause of mortality worldwide. The objective of the present study was to analyse the pattern of fatal head injury among patients seen in University College Hospital, Ibadan. The study was based on retrospective investigation of cases of fatal head injury referred by the coroner to the Department of Pathology, University College Hospital, between 1991 and 2000. Pertinent clinical and postmortem findings were extracted from available coroner's autopsy records. There were 529 cases (402… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
25
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 13 publications
13
25
1
Order By: Relevance
“…Among the cases studied, majority were males (77.27%) than females (22.72%). Similarly male predominance were observed by various researchers in their studies [2,3,4,5,6]. The peak incidence was observed in the age group of third and fourth decades (61.36%).…”
Section: Discussionsupporting
confidence: 77%
“…Among the cases studied, majority were males (77.27%) than females (22.72%). Similarly male predominance were observed by various researchers in their studies [2,3,4,5,6]. The peak incidence was observed in the age group of third and fourth decades (61.36%).…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings were observed by other researchers [13][14][15][16][17][18] except Akang et and Lai et al who observed that the peak age of such victims was in fourth decade. 19,20 This could be because young adults are the prime bread earners of the family and remain outdoors during most of the day. Furthermore, young people are by nature indulge in more violent activities.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] This finding, however, is at a discord with the situation in the US where falls were reported to be the leading etiologic factor. 9 Interpersonal violence accounts for 51% of nonfatal TBI among Africans, as against 10% for whites, while motor vehicle accidents cause 27% of African nonfatal TBI and 63% among whites.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…8 As has been previously reported by other local studies in Nigeria, the very active >20 -30 year group are the most commonly affected, majority being affected by mobilopathy especially motorcycle accidents. [10][11][12][13] This is as opposed to the 15 -19 years old peak incidence age in the US perhaps as a result of the fact that US youths drive cars at an earlier age than Nigerian youths who would usually take up motorcycle driving at this age. 15 Falls are shown to be a greater etiologic factor at the extremes of age and this is in agreement with most other studies.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%